Classical philosophy and philosophical critique. An essay on the relevance of philosophy - Echeverri Saldarriaga, Santiago (Estudios de Filosofía, 2001)
The article aims to answer to the question about the sense of philosophy in the present time. In order to do so, it is adopted the matter concerning the relevance of studying classical authors as a main idea. In such sense, the article aims to put forward that such study is an issue linked closely to the essence of the philosophy. For determining exactly this thesis is put forward that philosophical knowledge is neither scientific knowledge nor mere opinion. Once it is established philosophical knowledge as a critic one, the article expounds the reasons by which the study of classical authors is relevant in the present time. From this last point it follows that the study of classical philosophers allows to understand the present time itself giving thus a place for the scope of freedom. Il ends with a question about the view adopted in the article itself in order to answer the initial question.